2022
DOI: 10.1128/spectrum.02694-21
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Gram-Negative Bacteria and Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae from the Poultry Farm Environment

Abstract: The occurrence and spread of ARB due to high demand in poultry industries are of great public health concern. The widespread emergence of antibiotic resistance, particularly MDR among bacterial pathogens, poses challenges in clinical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Klebsiella spp. is an opportunistic Enterobacteriaceae that is highly pathogenic to poultry, livestock, and humans, and it is commonly found throughout China [25,26] as well as in other countries [27,28]. Here, Klebsiella contamination on the eggshell surfaces from the poultry farms was detected, with a season-dependent occurrence rate.…”
Section: Discussionmentioning
confidence: 89%
“…Klebsiella spp. is an opportunistic Enterobacteriaceae that is highly pathogenic to poultry, livestock, and humans, and it is commonly found throughout China [25,26] as well as in other countries [27,28]. Here, Klebsiella contamination on the eggshell surfaces from the poultry farms was detected, with a season-dependent occurrence rate.…”
Section: Discussionmentioning
confidence: 89%
“…A high frequency of resistance to ciprofloxacin, tetracycline, cefoxitin, amoxicillin/clavulanic acid, cefotaxime, and aztreonam was reported from water samples of the Mondego River in Portugal (Amador et al, 2015). Schmiege et al (2021); Zagui et al (2020); Veloo et al (2022) also observed MDR and ESBL-producing ARB in urban wastewaters. MAR index values for 12 isolates ranged between 0.21-0.75.…”
Section: Discussionmentioning
confidence: 97%
“…The emergence of antibiotic-resistant bacteria poses a challenge to human health, poultry industry, and aquaculture. Although the development of novel strategies to manage infections by antibiotic-resistant bacteria is urgently required, we should also be aware of how the acquisition of antibiotic resistance shapes the normal physiology of bacteria. Elucidation of antibiotic-resistant bacteria and host interactions may pave the way for understanding the threat of antibiotic resistance from different perspectives.…”
Section: Discussionmentioning
confidence: 99%